Green synthesis of gold nanoparticles using Euphrasia officinalis leaf extract to inhibit lipopolysaccharide-induced inflammation through NF-κB and JAK/STAT pathways in RAW 264.7 macrophages - Liu Y (Dove Medical Press, 2019)
Ying Liu,1 Senghyun Kim,2 Yeon Ju Kim,1,2 Haribalan Perumalsamy,2 Seungah Lee,3 Eunson Hwang,4 Tae-Hoo Yi1,2 1Graduate School of Biotechnology, College of Life Sciences, Kyung Hee University, Yongin-si, Gyeonggi-do, Republic of Korea; 2Department of Oriental Medicinal Biotechnology, College of Life Sciences, Kyung Hee University, 1732, Deogyeong-daero, Giheung-gu, Yongin-si, Gyeonggi-do 17104, Republic of Korea; 3Department of Applied Chemistry and Institute of Natural Sciences, College of Applied Science, Kyung Hee University, Yongin-si, Republic of Korea; 4Snow White Factory Co., Ltd., Gangnamgu, Seoul, Republic of Korea Background: Gold nanoparticles (AuNPs) have potential applications in the treatment and diagnosis process, which are attributed to their biocompatibility and high efficiency of drug delivery. In the current study, we utilized an extract of Euphrasia officinalis, a traditional folk medicine, to synthesize gold nanoparticles (EO-AuNPs), and investigated their anti-inflammatory effects on lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Materials and methods: The AuNPs were synthesized from an ethanol extract of E. officinalis leaves and characterized using several analytical techniques. Anti-inflammatory activities of EO-AuNPs were detected by a model of LPS-induced upregulation of inflammatory mediators and cytokines including nitric oxide (NO), inducible nitric oxide synthase (iNOS), tumor necrosis factor-α (TNF-α), IL-1β, and IL-6 in RAW 264.7 cells. The activation of nuclear factor (NF)-κB and Janus kinase/signal transducer and activators of transcription (JAK/STAT) signaling pathways was investigated by Western blot. Results: The results confirmed the successful synthesis of AuNPs by E. officinalis. Transmission electron microscopy images showed obvious uptake of EO-AuNPs and internalization into intracellular membrane–bound compartments, resembling endosomes and lysosomes by RAW 264.7 cells. Cell viability assays showed that EO-AuNPs exhibited little cytotoxicity in RAW 264.7 cells at 100 µg/mL concentration after 24 hours. EO-AuNPs significantly suppressed the LPS-induced release of NO, TNF-α, IL-1β, and IL-6 as well as the expression of the iNOS gene and protein in RAW 264.7 cells. Further experiments demonstrated that pretreatment with EO-AuNPs significantly reduced the phosphorylation and degradation of inhibitor kappa B-alpha and inhibited the nuclear translocation of NF-κB p65. In addition, EO-AuNPs suppressed LPS-stimulated inflammation by blocking the activation of JAK/STAT pathway. Conclusion: The synthesized EO-AuNPs showed anti-inflammatory activity in LPS-induced RAW 264.7 cells, suggesting they may be potential candidates for treating inflammatory-mediated diseases. Keywords: gold nanoparticles, Euphrasia officinalis, lipopolysaccharide, LPS, inflammatory, NF-κB, JAK/STAT